Effect of conservative treatment on greater trochanteric pain syndrome: a systematic review and network meta-analysis of randomized controlled trials - Si-Qi Wang; Ning-Yi Guo; Wei Liu; Hong-jie Huang; Bing-bing Xu; Jian-quan Wang (Journal of Orthopaedic Surgery and Research)
Abstract Objective Numerous studies have investigated conservative treatments for GTPS. However, there remains a lack of comparative analyses among treatment modalities, making it challenging to formulate the optimal conservative treatment strategy. This study aimed to compare conservative treatments for greater trochanteric pain syndrome (GTPS) in terms of their effectiveness in relieving pain and improving functional outcomes. Methods In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, the PubMed, Embase, Cochrane Library and ClinicalTrials.gov along with other databases were searched to identify relevant studies. The quality of the selected studies was evaluated using risk of bias assessments, and the data were extracted. Network meta-analysis was performed using random effects models to evaluate the effects of treatment modalities on pain reduction and functional improvement. The evidence of the included studies was evaluated using the Grading of Recommendations, Assessment, Development, and Evaluations framework. Results Nineteen RCTs involving 1701 participants were included. The risk of bias was assessed using Cochrane ROB2. The results of network meta-analysis revealed that exercise therapy yielded the most significant improvement on reducing pain scores measured using the NRS and enhancing functional outcomes measured using the VISA-G. Additionally, injection therapy showed significant advantages in improving functional outcomes measured by using the Harris Hip Scale. Discussion This study confirmed the significant efficacy of exercise programs on pain reduction and functional improvement in GTPS patients. Additionally, we identified the positive effects of injection therapy and physical modalities on managing pain and enhancing functional outcomes among GTPS patients. Owing to the limited number of included studies, comparing the effects of different conservative treatments remains challenging. Future studies should expand the quantity of RCTs to identify the optimal conservative treatment strategy for GTPS. Conclusion This study reaffirmed the superiority of exercise therapy in the treatment of GTPS and revealed the effectiveness of injection and physical modalities. As the number of studies increase, we anticipate more reliable conclusions to further optimize conservative treatment strategies for GTPS. Ultimately, our study can help clinicians determine the optimal conservative treatment for GTPS and may spur future research on conservative treatments for tendinopathy.